Descripción del desempeño de los lideres juveniles bajo el enfoque de liderazgo transformacional, en cuatro ciudades de Colombia. (2020)
Being leadership an issue of utmost importance for society in general, considering that when approaching the role, an individual has the ability to influence another, leading him to discover his potential and showing him the way to an adequate performance at a personal level or in Working with organizations and / or communities, the search for studies that show this sense begins and that serve as a guide for young leaders, taking transformational leadership as a training base. Therefore, the objective of this study is to describe the performance of youth leaders under the transformational leadership approach in the cities of Bogotá, Bucaramanga, Medellín, and Cúcuta.